Space allocation for coastal aquaculture in North Africa: Data constraints, industry requirements and conservation issues. (November 2015) - Brigolin, Daniele; Lourguioui, Hichem; Taji, Mohamed Amine; Venier, Chiara; Mangin, Antoine; Pastres, Roberto
Abstract: This paper presents a methodology for the selection of coastal sites for finfish cage farming, based on both satellite remotely sensed data and mathematical models. Such methodology can be applied, at screening level, also in areas where field data are lacking, and consists in two steps. In the first one, candidate areas are ranked according to criteria which take into account the risk of cage breaking due to wave actions and fish welfare requirements. This step involves the post-processing of satellite data and results of operational oceanographic models by means a multi-criteria methodology implemented in a GIS environment. In the second step, an integrated aquaculture impact assessment model is applied to the most suitable areas in order to obtain a preliminary assessment of the potential interaction of a newly established cage with benthic habitats. The methodology was applied to an Algerian coastal area near the town of Bejaia where the central government is planning to develop aquaculture activities. Results show that the procedure allows to perform a site selection, which combines the quality of a site from the aquaculture use perspective with the conservation of endangered benthic habitats ( Posidonia oceanica meadows) under the spatial restrictions imposed by existing activities. This result goes in the direction of defining site selection methodologies complying with the principles of the ecosystem approach to aquaculture and providing a science-based support in the framework of the implementation of the UNEP/MAP ecological approach. Highlights: Algerian government is planning to develop aquaculture activities in the study area. We merged site quality criteria with a preliminary evaluation of cage interactions. Operational oceanography and remote sensing supplied information to models.